Assessment of Blind-Spots and Multi-Path Effects at Indoor Positioning by Multilateration - N. Doğan; Ö. H. Bettemir (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Indoor positioning techniques are utilized in many professional applications. However, aforementioned technique can provide positions with serious accuracy problems due to multipath and ill-conditioned station constellations. In the literature the effect of multipath is examined thoroughly but the ill-conditioned station constellations are omitted. In this study, indoor positioning accuracy is examined by simulation where white Gaussian noise is added to the exact distances between the location to be measured and the station points. Effect of station constellation is analyzed by trying two different station positions. In the first case all of the stations are located at the same side of the room causing nearly parallel lines among the location and station points. In the second case all of the stations are located at different sides of the room and ill-conditioned systems are avoided. The simulation results provided that when the location to be measured and the stations are located at the same line, the measurement errors are magnified by the ill-conditioned least square-adjustment equations which leads to significant positioning errors. Moreover, an algorithm for the detection of multipath is proposed and tested by simulation. The algorithm detected 31 multipath cases among the 35 multipath situations and significantly improved the resultant positioning accuracy. The simulation results illustrated that the proposed multipath detection algorithm can be utilized efficiently for indoor positioning applications.